The Effect of Promo Price and Product Variation on Purchasing Decision at Grabfood, OVO Payment as an Intervening Variables - Supanji Setyawan; Suci Nasehati S; Agustina Prativi (Nusantara Science and Technology Proceedings, 2020)
The use of devices to transact anywhere and anytime makes consumers not have to bother to meet their needs. Payment methods can be cash or e-money, in this case, Grab applies for non-cash payments in collaboration with the OVO digital payment. The purpose of this study was to determine whether there was an effect of promo prices and product variations on buying decisions on the Grabfood application through the OVO payment method. The research method used is descriptive quantitative with multiple linear regression, with the stages of collecting data with a questionnaire given to Grabfood customers who use OVO. This research reveals that digital OVO payments can boost transactions in online businesses. The results of this study indicate an analysis of the effect of product variation through the OVO payment method on purchasing decisions. It can be explained that the direct effect of product variation on buying decisions is 0.323. Meanwhile, the indirect effect of product variation through the OVO payment method on purchasing decisions was 0.778, while the total effect was 1.101. So it can be concluded that indirect product variations through the OVO payment method have a significant effect on purchasing decisions.